Long-term changes in coarse woody debris abundance in three Appalachian headwater streams with differing best management practices - Sena, Kenton L.; Flynn, Jerrica K.; Leuenberger, Wendy; Kolka, Randall; Barton, Christopher D. (Frontiers in Forests and Global Change, 2023)
Introduction Timber harvests influence coarse woody debris (CWD) dynamics both initially and long-term—contributing a significant amount of CWD as slash immediately after harvest, but also removing some or all of the mature trees necessary to produce CWD over time. Whereas shelterwood and other similar timber harvest systems retain varying amounts of the overstory, preserving CWD production after harvest, commercial clearcutting essentially eliminates sources of fresh CWD until regenerating trees are large enough to contribute CWD through fallen limbs or trunks, often decades after harvest. Forestry best management practices (BMPs) are critical for reducing the water quality impacts of timber harvest, but their effects on riparian and stream CWD are not well understood. Methods The current project explores CWD dynamics (surveyed in 2001, 2004, 2009, and 2020) in three eastern Kentucky watersheds receiving differing timber harvest treatments in 1983: unharvested control, BMPs (clearcut with a protected streamside management zone), and no BMPs (clearcut). Results Analysis of hydrology data over the period of record demonstrated significant flooding in 2004 that likely “reset” CWD in the study watersheds. Coarse woody debris volume was higher in control (3.33 m3/ha) than no BMP (1.03 m3/ha) in 2020, with CWD accumulation rates ranging from 0.039 m3/ha in the no BMP watershed to 0.19 m3/ha in the control. Discussion While not significantly different, CWD volume was nominally higher in the BMP watershed than the No BMP watershed, suggesting that, in addition to their many other benefits, streamside management zones help facilitate CWD provisioning during stand initiation after a commercial clearcut harvest. Furthermore, this study suggests that provisioning of CWD may not recover after clearcut harvesting for 100 years or more.